1977
DOI: 10.1128/aem.33.2.379-384.1977
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological profiles of the Viking spacecraft

Abstract: Planetary quarantine requirements associated with the launch of two Viking spacecraft necessitated microbiological assessment during assembly and testing at Cape Canaveral and the Kennedy Space Center. Samples were collected from selected surfaces of the Viking Lander Capsules (VLC), Orbiters (VO), and Shrouds at predetermined intervals during assembly and testing. Approximately 7,000 samples were assayed. Levels of bacterial spores per square meter on the VLC-1 and VLC-2 were 1.6 x 102 and 9.7 x 10', respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…There were no Eukarya found in the SAEF‐II samples, though seven strains of the fungus Aureobasidium pullulans were retrieved from the spacecraft samples . As observed in this communication, several culture‐dependent studies revealed that the microbial species recovered from air and surface samples in the clean‐room encapsulation facilities at the Kennedy Space Center are nearly identical to species recovered from surfaces of an unpiloted spacecraft (Favero et al ., 1966; Favero, 1971 ; Puleo et al ., 1977; Vasin and Trofimov, 1995). The elevated level of diversity seen in this study on the spacecraft surfaces might be attributed to the fact that the manufacturing and integration of various hardware components took place across various geographic regions prior to the final assembly at the KSC SAEF‐II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no Eukarya found in the SAEF‐II samples, though seven strains of the fungus Aureobasidium pullulans were retrieved from the spacecraft samples . As observed in this communication, several culture‐dependent studies revealed that the microbial species recovered from air and surface samples in the clean‐room encapsulation facilities at the Kennedy Space Center are nearly identical to species recovered from surfaces of an unpiloted spacecraft (Favero et al ., 1966; Favero, 1971 ; Puleo et al ., 1977; Vasin and Trofimov, 1995). The elevated level of diversity seen in this study on the spacecraft surfaces might be attributed to the fact that the manufacturing and integration of various hardware components took place across various geographic regions prior to the final assembly at the KSC SAEF‐II.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that spore‐formers are the most common type of microbes isolated from surfaces of various spacecraft (Favero, 1971; Puleo et al ., 1973; 1975). A few studies have been conducted on the microbial ecology of spacecraft assembly and encapsulation facilities (Favero et al ., 1966, 1968b; Venkateswaran et al ., 2001), and it has been suggested that the level of microbial diversity and overall microbial burden associated with a spacecraft may be inferred from studying the microbial ecology of the facility where assembly and encapsulation take place (Puleo et al ., 1977).…”
Section: Introductionmentioning
confidence: 99%
“…These organisms are representative strains of the endospore producing Bacillus sp. [14,17,[30][31][32][33][34]. Both strains produce spores that exhibit unusual levels of resistance to peroxide and UV radiation [25,30,35] that far exceed that of the dosimetric B. subtilis type strain (B. subtilis subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary sources of contamination are controlled by good manufacturing practices and standard industrial practices. The microbes of concern in SAF are primarily spore-forming bacteria and microbes that are indigenous to human skin, hair, and respiratory tract (Puleo et al, 1977). Bacterial spores, particularly those in the Bacillus genus, are common in the spacecraft industry.…”
mentioning
confidence: 99%